The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1073/pnas.1934572100
|View full text |Cite
|
Sign up to set email alerts
|

The first external loop of the metal ion transporter DCT1 is involved in metal ion binding and specificity

Abstract: The yeast null mutant smf1⌬ cannot grow on medium containing EGTA. Expression of Smf1p or the mammalian transporter DCT1 (Slc11a2) suppresses the above-mentioned phenotype. Both can also be expressed in Xenopus oocytes, and the uptake activity and their electrophysiological properties can be studied. We used these systems to analyze the properties of mutations in the predicted external loop I of DCT1. The sensitivity of the transporter to amino acid substitutions in this region is manifested by the mutation G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Both use protons as their motive force to transport a broad-range of the same divalent metal ions and exhibit similar affinities for their various substrates (8,12,16). The mammalian DCT1 complements the phenotype of SMF1 null mutation in yeast (5,(17)(18)(19). The null mutant smf1⌬ is unable to grow in the presence of EGTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both use protons as their motive force to transport a broad-range of the same divalent metal ions and exhibit similar affinities for their various substrates (8,12,16). The mammalian DCT1 complements the phenotype of SMF1 null mutation in yeast (5,(17)(18)(19). The null mutant smf1⌬ is unable to grow in the presence of EGTA.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between the two homologues have to be due to the non-conserved amino acids in both proteins. Consequently, to locate the sites on the transporters responsible for this phenomenon, we substituted amino acids in DCT1 for the corresponding ones residing in Smf1p (19). It has been found that a mutation in the conserved glycine at position 216 (G216R) in the putative TM4 of DCT1 causes microcytic anemia in mkϪ/Ϫ mice and Belgrade rats (20).…”
Section: Resultsmentioning
confidence: 99%
“…The TMS1 Asp residue is part of a conserved DPGN motif that has been subjected to mutagenesis in studies using MntH or Nramp2 homologs, which showed loss of Me 2ϩ uptake caused by Gly exchange (11,47). The carboxyl end of Nramp2 TMS1 and adjacent extra loop were implicated in Me 2ϩ binding and coupling of Me 2ϩ uptake to the proton-motive force ((C/S/T)P(C/H)) that is conserved in the TMS6 of P 1B -type ATPases, which pump heavy metal cations using energy provided by ATP hydrolysis (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of leucine uptake: The method described in cued by a tor1 allele defective in rapamycin binding: If Karagiannis et al (1999) was followed with slight modifications adopted from Cohen et al (2003). rapamycin sensitivity in auxotrophs is the result of TOR or ⌬tor1 cells (TA390) were grown to log phase in minimal inhibition by FKBP12-rapamcin, it is expected that mumedium.…”
Section: Rapamycin Sensitivity Of Leucine Auxotrophs Is Res-mentioning
confidence: 99%